ProcSoft: A Board Game to Teach Software Processes Based on ISO/IEC 29110 Standard - Moura, Victor; Santos, Gleison (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Software development processes must support all activities from requirements elicitation to product release and address software engineering best practices. International standards provide important, comprehensive and correct knowledge to help defining good software processes, but they are written in formal language, and their presentation are not easily assimilated by students. ProcSoft is a board game defined to promote software processes definition based on ISO/IEC 29110 standard. It has been used for several terms on Software Engineering classes. Complementary post-game activities aim at fostering content assimilation: students must answer software engineering questions in class, define a software development process and simulate its use. We present evaluation results evidencing great students' involvement during classroom activities, their acknowledgement of both ProcSoft contribution to learning, and its positive influence to foster the search for additional knowledge outside the classroom.